2021
DOI: 10.1021/acs.inorgchem.1c03183
|View full text |Cite
|
Sign up to set email alerts
|

Efficacious CO2 Adsorption and Activation on Ag Nanoparticles/CuO Mesoporous Nanosheets Heterostructure for CO2 Electroreduction to CO

Abstract: It is an ongoing pursuit for researchers to precisely control the catalyst’s surface for high-performance CO2 electrochemical reduction (CO2ER). In this work, CuO mesoporous nanosheets (CuO MNSs) with rough edges decorated by small Ag nanoparticles (Ag NPs) with a tunable amount of Ag were synthesized on a Cu foil at normal atmospheric temperature through two-step solution-phase reactions for CO2ER to CO. In this special Ag NPs/CuO MNSs heterostructure, the mesoporous CuO NSs with rough edges favored gas infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In Figure S6, there were three peaks at 269, 320, and 605 cm −1 corresponding to the A g , B g1 , and B g2 modes of the CuO crystal on CuO nanosheets, respectively. 28 Obviously, the three peaks shifted to higher wavenumbers for V o -CuO(Sn), and a new weak peak that appeared at 485 cm −1 could be assigned to the E g mode of SnO 2 . 29 Therefore, by combining the XPS, ICP-OES, and Raman results, it could be concluded that Sn atoms were successfully introduced into the CuO lattice by partially replacing the positions of the Cu atoms.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In Figure S6, there were three peaks at 269, 320, and 605 cm −1 corresponding to the A g , B g1 , and B g2 modes of the CuO crystal on CuO nanosheets, respectively. 28 Obviously, the three peaks shifted to higher wavenumbers for V o -CuO(Sn), and a new weak peak that appeared at 485 cm −1 could be assigned to the E g mode of SnO 2 . 29 Therefore, by combining the XPS, ICP-OES, and Raman results, it could be concluded that Sn atoms were successfully introduced into the CuO lattice by partially replacing the positions of the Cu atoms.…”
Section: Resultsmentioning
confidence: 92%
“…To further confirm the successful doping of Sn elements, Raman spectra of CuO and V o -CuO­(Sn) samples were performed. In Figure S6, there were three peaks at 269, 320, and 605 cm –1 corresponding to the A g , B g1 , and B g2 modes of the CuO crystal on CuO nanosheets, respectively . Obviously, the three peaks shifted to higher wavenumbers for V o -CuO­(Sn), and a new weak peak that appeared at 485 cm –1 could be assigned to the E g mode of SnO 2 .…”
Section: Resultsmentioning
confidence: 96%
“…The excellent ECR activity is attributed to the more active sites and good mass transfer of nanosized catalyst(Figure 2a-c) . Zhang et al [41] presented an Ag nanoparticles decorated CuO mesoporous nanosheets with rough edges growing on the surface of copper foil (Ag NPs/CuO MNSs). The FE for CO is 91.2 % with a partial current density of 10.5 mA cm -2 at an applied potential of -0.7 V (vs.RHE).…”
Section: Products Of Co and Hcooh/hcoo -Catalyzed By Od-cumentioning
confidence: 99%
“…Zhang and co‐workers used two‐step solution‐phase reactions to synthesize Ag 1.01% /CuO. A tunable amount of Ag NPs were decorated on the mesoporous CuO nanosheets (CuO MNSs) with rough edges [71] . The mesoporous CuO NSs favor gas infiltration, and Ag NPs expand the active sites for CO 2 adsorption and endow good electrical conductivity for the special heterostructure.…”
Section: Ag‐based Materialsmentioning
confidence: 99%
“…A tunable amount of Ag NPs were decorated on the mesoporous CuO nanosheets (CuO MNSs) with rough edges. [71] The mesoporous CuO NSs favor gas infiltration, and Ag NPs expand the active sites for CO 2 adsorption and endow good electrical conductivity for the special heterostructure. Therefore, the optimal Ag 1.01% / CuO can catalyze CO 2 to CO with a FE CO of 91.2% and CO partial current density of 10.5 mA cm À 2 at À 0.7 V. Moreover, it can retain 97.8% of the initial current density and 97.6% of the original FE CO for CO after 12 h testing at À 0.7 V, demonstrating a prominent catalytic stability.…”
Section: Ag/metal Oxides Compositesmentioning
confidence: 99%